ANALYSIS OF THE IMPACT OF FINTECH AND PRICE STABILITY IN ENHANCING ECONOMIC GROWTH: EVIDENCE IN JAVA - Salma, Citra Naura Putri; Putri, Risqi Noor Hidayati (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2025)
Purpose The objective of this study is to analyze the impact of financial technology (fintech) and price stability on economic growth in Java Island. This research examines how fintech transactions, measured through electronic money volume, influence financial efficiency and economic inclusivity. Design/methodology/approach This study employs a quantitative approach using panel data regression analysis from 2019 to 2023. The dataset includes fintech transaction volume, technology adoption rates, and CPI from six provinces in Java. Findings This study examines the interplay between fintech transactions, technology adoption, and price stability in driving economic growth in Java. While fintech improves financial inclusion, its dominance in consumptive transactions negatively impacts economic growth, highlighting the need for a shift toward productive financial activities. Research limitations/implications This study focuses on six provinces in Java, limiting its applicability to regions with lower digital penetration. Additionally, it does not differentiate between productive and consumptive fintech transactions, making it difficult to assess fintech’s true economic impact. Originality/value This research fills the gap in understanding the dual impact of fintech on economic growth—highlighting the negative consequences of excessive consumptive transactions while demonstrating the positive role of ICT and price stability.